2008
DOI: 10.1002/ajmg.b.30858
|View full text |Cite
|
Sign up to set email alerts
|

Prepulse inhibition in fragile X syndrome: Feasibility, reliability, and implications for treatment

Abstract: Background-Pharmacological rescue of behavioral, cognitive and synaptic abnormalities in the animal models of fragile X syndrome (FXS) has prompted the initiation of clinical trials of targeted treatments in humans with this condition. Objective, well-validated outcome measures that are reflective of FXS deficits and can be modeled similarly in animal and human studies are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
69
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 64 publications
6
69
1
Order By: Relevance
“…Furthermore, one study in Fmr1 KO mice has shown decreased PPI of startle eyelid responses with the magnetic distance measurement [23]. This correlates with findings in humans with FXS [54,55], and thus supports a role for FMRP in sensorimotor processing both in humans and mice. Interestingly, recent studies using THIP, which we have shown to have amygdala effects [18], have also demonstrated the existence of a potent tonic inhibitory neurotransmission in the rat auditory thalamus [56] and in the avian nucleus laminaris [57], suggesting an active role of tonic inhibition in modulating auditory processing cues.…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, one study in Fmr1 KO mice has shown decreased PPI of startle eyelid responses with the magnetic distance measurement [23]. This correlates with findings in humans with FXS [54,55], and thus supports a role for FMRP in sensorimotor processing both in humans and mice. Interestingly, recent studies using THIP, which we have shown to have amygdala effects [18], have also demonstrated the existence of a potent tonic inhibitory neurotransmission in the rat auditory thalamus [56] and in the avian nucleus laminaris [57], suggesting an active role of tonic inhibition in modulating auditory processing cues.…”
Section: Discussionsupporting
confidence: 61%
“…We also suggest that outcome measures that have been documented to be abnormal in fragile X syndrome, and have been shown to be helpful in other targeted treatment trials in fragile X syndrome, should be utilized for controlled trials of minocycline (Berry-Kravis et al, 2009; Farzin, Rivera, & Hessl, 2009; Farzin, Whitney, Hagerman, & Rivera, 2008; Hessl et al, 2009). Such quantitative measures include prepulse inhibition, which is a neurophysiological assessment of frontal gating.…”
Section: Discussionmentioning
confidence: 99%
“…Fragile X syndrome, caused by a mutation in FMRI gene at Xq27.3, which prevents normal transcription with subsequent reduction/absence of FMRI protein (Tamanini et al 1997), and aberrant dendritic arborization and synaptic plasticity (Irwin et al 2000;Galvez and Greenough 2005), presents serious cognitive deficits and behavioral retardation (Cornish et al 2001;Hoeft et al 2007;Mercaldo et al 2009;Sharma et al 2009). Hessl et al (2009) assessed PPI of the startle reflex in 61 individuals with the fragile X full mutation (40 males and 21 females) with 63 age-matched normal healthy controls. They found that, in comparison with normal controls, fragile X individuals displayed PPI impairments of 26, 22, and 28% for the 60, 120, and 240 ms prepulse interval trial types, respectively, with markedly high levels of test-retest reliability.…”
Section: Epigenetics and Prepulse Inhibitionmentioning
confidence: 99%